2021
DOI: 10.3171/2020.10.jns203323
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insula stimulation increases pain threshold in humans: a pilot study

Abstract: OBJECTIVE Chronic pain results in an enormous societal and financial burden. Opioids are the mainstay of treatment, but opioid abuse has led to an epidemic in the United States. Nonpharmacological treatment strategies like deep brain stimulation could be applied to refractory chronic pain if safe and effective brain targets are identified. The anterior insula is a putative mediator of pain-related affective-motivational and cognitive-evaluative cerebral processing. However, the effect of anterior insula stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…60,61 Finally, while this review focused on sEEG research of psychiatric-related behaviors, it is imperative to note that sEEG is a powerful research instrument for studying the spatiotemporal dynamics of neural circuits contributing to other cognitive processes or diseases, such as chronic pain, movement disorders, speech, memory, sleep, and arousal. [62][63][64] Furthermore, the studies included in this review have demonstrated the powerful application of machine learning algorithms to iEEG data, which will strengthen our understanding of the neural networks underlying human behaviors.…”
Section: Discussionmentioning
confidence: 94%
“…60,61 Finally, while this review focused on sEEG research of psychiatric-related behaviors, it is imperative to note that sEEG is a powerful research instrument for studying the spatiotemporal dynamics of neural circuits contributing to other cognitive processes or diseases, such as chronic pain, movement disorders, speech, memory, sleep, and arousal. [62][63][64] Furthermore, the studies included in this review have demonstrated the powerful application of machine learning algorithms to iEEG data, which will strengthen our understanding of the neural networks underlying human behaviors.…”
Section: Discussionmentioning
confidence: 94%
“…However, this phenomenon is not present in every region of the pain matrix. The insula, as an essential node of the salience network as well as the pain matrix, improves individual brain-based pain sensitivity and increases thresholds for human pain, and is an important part of the brain involved in processing pain [ 50 52 ]. The cerebellum is commonly thought to be associated with movement, and the cerebellum supports experimental pain and chronic pain processing with its complex sensory, emotional, and neurocognitive aspects [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low frequency electrical stimulation of the right pI elicits nociception in humans and primates with some somatotopy ( Ostrowsky et al, 2002 ; Mazzola et al, 2009 ), while high frequency stimulation of pI and aI reduces pain thresholds with no obvious side effects, consistent with insular inactivation ( Denis et al, 2016 ; Liu et al, 2021 ). A form of rTMS in IC has been shown to produce bilateral thermal analgesia in humans without affecting the ability to perceive innocuous thermal or vibrotactile sensations ( Lenoir et al, 2018 ).…”
Section: Future Outlookmentioning
confidence: 94%